A study of adherence to treatment and influencing factors it in patients with ischemic heart disease - Yusupov Rustamjon B; Nuritdinova Nigora B; Bazarov Elbek Sh (Zien Journals, 2024)
Adherence to treatment in patients with ischemic heart disease was studied. The study was conducted in 108 patients aged 55-68 years. A special questionnaire was distributed to each patient and the obtained results were studied. Adherence to treatment was compared between stented patients and drug-only patients. Also, in order to study the factors affecting patients' adherence to treatment, a special questionnaire was prepared and the patients' answers were recorded. In this way, the most important factors affecting the adherence of patients to treatment were determined.
Keywords: Ischemic heart disease; adherence to treatment; stenting of coronary vessels